PERAN ORANGTUA TERHADAP AKTIVITAS PENDIDIKAN ANAK SELAMA PEMBELAJARAN JARAK JAUH - Tiara Desicha; Ansoriyah, Siti (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2022)
Parents have a very important role in the learning process of children during distance learning at this time, are also very instrumental in providing education and supervising their children who still do not understand about the pandemic who is at home so that they are not infected and endemic to remain silent at home. house so as not to contract and spread the covid-19 virus. Parents who study at home are very effective to implement, but that does not mean learning at school is no more effective than learning activities at home. The purpose of this study was to see the role of parents in children’s learning activities at home during the Covid 19 pandemic which is focused on children aged 5-8 years. This research method is to use a phenomenological qualitative method. The results of this study are that parents can improve their relationship with their children and parents can see directly the development of their children’s learning abilities.